2021
DOI: 10.21037/atm-21-1438
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term chest CT follow-up in COVID-19 Survivors: 102–361 days after onset

Abstract: Background: The aim of this study was to evaluate long-term longitudinal changes in chest computed tomography (CT) findings in coronavirus disease 2019 survivors and their correlations with dyspnea after discharge.Methods: A total of 337 COVID-19 survivors who underwent CT scan during hospitalization and between 102 and 361 days after onset were retrospectively included. Subjective CT findings, lesion volume, therapeutic measures and laboratory parameters were collected. The severity of the survivors' dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Survivors with dyspnea had a significantly higher lesion volume on the CT scan, while the absorption of lesions continued to persist 6 months following hospital discharge [ 23 ]. Besides persistent respiratory complaints, patients with long COVID also showed continuously significantly higher values of c-reactive protein, fibrinogen, urea, and creatinine associated with abnormal imaging findings [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survivors with dyspnea had a significantly higher lesion volume on the CT scan, while the absorption of lesions continued to persist 6 months following hospital discharge [ 23 ]. Besides persistent respiratory complaints, patients with long COVID also showed continuously significantly higher values of c-reactive protein, fibrinogen, urea, and creatinine associated with abnormal imaging findings [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis was conducted separately by different definitions of breathlessness: no scale (71 papers), MRC or mMRC dyspnoea scale (22 papers) and other scales (14 papers); 5 of the 102 papers measured post-COVID breathlessness using more than one definition. The pooled prevalence of post-COVID breathlessness was 26% (95% CI [23][24][25][26][27][28][29] in studies directly measuring presence or absence of the symptom, 41% (95% CI [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] in studies using MRC/mMRC dyspnoea scale and 51% (95% CI [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] in studies using other scales (figure 2). Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001).…”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001). ASADI-POOYA [24] AUL [91] AYDIN [65] BALDINI [62] FERNÁNDEZ-DE-LAS-PEÑAS [105] SUÁREZ-ROBLES [128] DARCIS [101] DREYER [103] ZAYET [137] YOMOGIDA [34] VENTURELLI [135] VARGHESE [134] TAYLOR [131] TAWFIK [14] SZEKELY [66] SULTANA [129] STAVEM [127] SONNWEBER [58] RIGHI [123] PELUSO [13] O'SULLIVAN [122] O'KEEFE [121] NAIK [54] MOTIEJUNAITE [64] MECHI [44] MALLIA [115] KLEIN [111] GABER [106] EROL [25] DIAZ-FUENTES [102] DANKOWSKI [100] CARFI [96] CORTÉS-TELLES [69] CARVALHO-SCHNEIDER [97] BOARI [94] VIJAYAKUMAR [65] Total (I 2 =95.9%, p<0.001) ZHANG [39] D'CRUZ [35] D'CRUZ [35] TODT [132] TAYLOR [131] SKJORTEN [38] DAYNES [10] APARISI [26] DE GRAAF [61] YIN …”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…Somatic sequelae of acute COVID-19 , e.g., persistent dyspnea by impaired pulmonary function [ 20 ] in patients with previously healthy lungs or loss of smell/taste that can persist for an undetermined period of time.…”
Section: Discussionmentioning
confidence: 99%